2011
DOI: 10.1016/j.jval.2011.02.563
|View full text |Cite
|
Sign up to set email alerts
|

Pdb55 Clinical and Economic Evaluation of a Diabetes Medication Management Program: 2 Year Program Update

Abstract: RESULTS:A total of 1185 established T2DM patients were assessed. The mean (SD) age was 55 (10) years and mean duration of diabetes (SD) of 10 (7) years. Metformin was the most commonly prescribed drug [827 (70%)], in general followed by insulin [627 (53%)], sulfonylureas [520 (44%)], and pioglitazone [329 (28%)]. A total of 348 (29%) patients received monotherapy and 837 (71%) received combination therapy. The most frequently prescribed monotherapy was insulin [214 (62%)], followed by metformin in 81 (23%), su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…104,105 When provided, pharmacist services were effective for smoking cessation, 25,104,105 identifying and resolving drug-related problems, 50,51,66,94,139,141 and improving clinical parameters such as glycosylated hemoglobin (HbA1c), cholesterol and blood pressure. 45,50,51,69,81,95 However, 1 study of Medicare Part D medication therapy management services found mixed clinical outcomes. 142 Pharmacist services were also widely considered to have a net cost benefit, 50,66,70,71,80,81,94,140,[142][143][144][145] with estimated returns on investment from the payer perspective ranging from $1.29 per dollar spent within the Minnesota Medication Therapy Management Program 50 to $2.50 per dollar spent in a Medicare Part D Medication Therapy Management Program.…”
Section: Clinical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…104,105 When provided, pharmacist services were effective for smoking cessation, 25,104,105 identifying and resolving drug-related problems, 50,51,66,94,139,141 and improving clinical parameters such as glycosylated hemoglobin (HbA1c), cholesterol and blood pressure. 45,50,51,69,81,95 However, 1 study of Medicare Part D medication therapy management services found mixed clinical outcomes. 142 Pharmacist services were also widely considered to have a net cost benefit, 50,66,70,71,80,81,94,140,[142][143][144][145] with estimated returns on investment from the payer perspective ranging from $1.29 per dollar spent within the Minnesota Medication Therapy Management Program 50 to $2.50 per dollar spent in a Medicare Part D Medication Therapy Management Program.…”
Section: Clinical Reviewmentioning
confidence: 99%
“…45,50,51,69,81,95 However, 1 study of Medicare Part D medication therapy management services found mixed clinical outcomes. 142 Pharmacist services were also widely considered to have a net cost benefit, 50,66,70,71,80,81,94,140,[142][143][144][145] with estimated returns on investment from the payer perspective ranging from $1.29 per dollar spent within the Minnesota Medication Therapy Management Program 50 to $2.50 per dollar spent in a Medicare Part D Medication Therapy Management Program. 144 Patient satisfaction, when measured, was high, 50,142,146,147 as was job satisfaction among U.K. pharmacists performing Medication Use Reviews.…”
Section: Clinical Reviewmentioning
confidence: 99%